Implementasi Fault Tolerant System Menggunakan Metode Self-Purging Redundancy Pada Sistem Pendeteksi Kebakaran - Irfani Fadlan; Rakhmadhany Primananda; Wijaya Kurniawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2020)
Fire can occur anytime, anywhere and it cannot be predicted. When this disaster occurs, it can cause material, non-material loss and even cause casualties. Current fire detection systems ranging from flame detectors and even sprinklers can detect signs of a fire. But when there are component errors, the system cannot function as it should. System failures can occur when these errors continue continuously. The application of fault tolerant systems with hardware redundancy techniques is the solution for the problems above. Self-purging redundancy is one of the methods found in hardware redundancy. This method is applied by reducing the microcontroller data processing MQ-2 gas sensor, KY-026 fire sensor and LM35 temperature sensor. Using I2C communication data is forwarded to the switch and collected in the voter to be voted on with the majority vote logic. The result data of vote is used by the system as a determinant of the fire conditions and displayed on the LCD, then the voter returns the results of the vote to the switch for validation of a failed module. If a module failure is detected, the module will be removed from the system. From testing, the system successfully operates correctly in accordance with its functions and successfully performs fault masking, detection and location and recovery when the 3-module scan fails. Increased system reliability by 16.17% from 83.51% to 99.68%.